Variable Cognition in ABM Decision-Making: An Application to Livestock Vaccine Choice - Iles, Richard A.; Sottile, Matthew J.; Amram, Ofer; Lofgren, Eric; McConnel, Craig S. (Frontiers in Veterinary Science, 2020)
Modeling realistic human decision-making is an important feature of good policy design processes. The use of an agent-based modelling framework allows for quantitative human decision-models that assume fully rational agents. This research introduces a dynamic human decision-making sub-model. The parameterisation of human memory and ‘rationality’ in a decision-making model represents an important extension of decision-making in ABMs. A data driven model of herd movement within a dynamic natural environment is the context for evaluating the cognitive decision-making model. The natural and human environments are linked via memory and rationality that affect herdsmen decision-making to vaccinate cattle using a once-for-life vaccine (Rift Valley fever) and an annual booster vaccine (Contagious Bovine Pleuropneumonia). The simulation model uses environmental data from Samburu county, Kenya from 2004 to 2015. The cognitive parameters of memory and ‘rationality’ are shown to successfully differentiate between vaccination decisions that are characterised by annual and once-for-life choices. The preliminary specifications and findings from the dynamic cognition - pastoralist agent-based model (PastoralScape) indicate that the model offers much to livestock vaccination modelling among small-scale herders.